Implementation of Audiolingual Method as Instructional Media in Improving English Speaking Skills - Situmorang, Idawati; Sitompul, Hamela Sari; Tuty (ITScience (Information Technology and Science), 2024)
This research aims to determine whether the use of the Audio-visual method has a significant influence on English speaking skills. The sample of this study was 21 first-semester students in the English course at AMIK Parbina Nusantara. The approach used was qualitative, and the type of classroom action research (CAR) consists of 3 cycles, each composed of the stages of activities including planning, implementation, observation, and reflection. This study focuses on applying the audiolingual method as a medium of instruction to improve students' English speaking skills. The results of the study showed that there was an increase in student learning activities and learning outcomes. This study concludes that the audio-visual method as a medium of instruction improves the speaking skills of AMIK Parbina Nusantara students.